ANALISIS INKLUSI KEUANGAN DAN PEMERATAAN PENDAPATAN DI INDONESIA - Bintan Badriatul Ummah; Nunung Nuryartono; Lukytawati Anggraeni (IPB University, 2015)
Recent study showed that increasing access and usage of banking services reduce income inequality. Nowdays banking access in Indonesia is increasing but income equality gap is widening. Therefore, by using secondary data from 33 provinces 2007- 2011, this paper aims to measure the level of access and usage for financial services across provinces in Indonesia by Index of Financial Inclusion, analyze the factors that affect financial inclusion by panel tobit regression, and describe the relationship between financial inclusion and income distribution in Indonesia. The results show that the level of financial inclusion in Indonesia is classified as low. The size of the economy and income inequality positively affect the level of financial inclusion. Opposite the research hypothesis, widening income inequality lead to higher financial inclusion in Indonesia. Moreover, the number of mobile phone and the internet user affect positively the level of financial inclusion in Indonesia. Income inequality and financial inclusion has a one-way relationship, income inequality affects financial inclusion in Indonesia but does not vice versa. Keywords : Financial Inclusion, income inequality